Tracing the origin of the oxygen-consuming organic matter in the hypoxic zone in a large eutrophic estuary: the lower reach of the Pearl River Estuary, China - J. Su; M. Dai; B. He; B. He; L. Wang; J. Gan; X. Guo; H. Zhao; F. Yu (Biogeosciences, 2017)
We assess the relative contributions of different sources of organic matter, marine vs. terrestrial, to oxygen consumption in an emerging hypoxic zone in the lower Pearl River Estuary (PRE), a large eutrophic estuary located in Southern China. Our cruise, conducted in July 2014, consisted of two legs before and after the passing of Typhoon Rammasun, which completely de-stratified the water column. The stratification recovered rapidly, within 1 day after the typhoon. We observed algal blooms in the upper layer of the water column and hypoxia underneath in bottom water during both legs. Repeat sampling at the initial hypoxic station showed severe oxygen depletion down to 30 µmol kg−1 before the typhoon and a clear drawdown of dissolved oxygen after the typhoon. Based on a three endmember mixing model and the mass balance of dissolved inorganic carbon and its isotopic composition, the δ13C of organic carbon remineralized in the hypoxic zone was −23.2 ± 1.1 ‰. We estimated that 65 ± 16 % of the oxygen-consuming organic matter was derived from marine sources, and the rest (35 ± 16 %) was derived from the continent. In contrast to a recently studied hypoxic zone in the East China Sea off the Changjiang Estuary where marine organic matter dominated oxygen consumption, here terrestrial organic matter significantly contributed to the formation and maintenance of hypoxia. How varying amounts of these organic matter sources drive oxygen consumption has important implications for better understanding hypoxia and its mitigation in bottom waters.